A novel bis-triazole scaffold accessed via two tandem [3 + 2] cycloaddition events including an uncatalyzed, room temperature azide–alkyne click reaction - Malkova, Ksenia; Bubyrev, Andrey; Krivovicheva, Vasilisa; Dar’in, Dmitry; Bunev, Alexander; Krasavin, Mikhail (Beilstein Journal of Organic Chemistry, 2022)
The previously described α-acetyl-α-diazomethanesulfonamide was employed in a three-component reaction with azide-containing benzaldehydes and propargylamines. Besides the initial formation of the triazole core, the reaction proceeded further, in uncatalyzed fashion at room temperature and yielded, after intramolecular azide–alkyne click reaction novel, structurally intriguing bistriazoles.
Keywords: α-acetyl-α-diazomethane sulfonamide; intramolecular click reaction; uncatalyzed; room temperature; 1,2,3-triazoles

(untitled) - Serafini, M.; Pirali, T.; Tron, G. C. (Adv. Heterocycl. Chem., 2021)

(untitled) - Agalave, S. G.; Maujan, S. R.; Pore, V. S. (Chem. – Asian J., 2011)

(untitled) - Nemallapudi, B. R.; Guda, D. R.; Ummadi, N.; Avula, B.; Zyryanov, G. V.; Reddy, C. S.; Gundala, S. (Polycyclic Aromat. Compd., 2022)

(untitled) - Bubyrev, A.; Malkova, K.; Kantin, G.; Dar’in, D.; Krasavin, M. (J. Org. Chem., 2021)

(untitled) - Bubyrev, A.; Adamchik, M.; Dar’in, D.; Kantin, G.; Krasavin, M. (J. Org. Chem., 2021)

(untitled) - Devaraj, N. K.; Finn, M. G. (Chem. Rev., 2021)

PCT Int. Appl. - Mekonnen, B.; Butera, J. A.; Huang, J.; Patel, H.; Jiang, Q.; Herr, R. J.; Mayhew, N. J.; Freeman, E. E. (Benzodiazepine Derivatives, Compositions, And Methods for Treating Cognitive Impairment, 2019)

(untitled) - Sheppard, G. S.; Wang, L.; Fidanze, S. D.; Hasvold, L. A.; Liu, D.; Pratt, J. K.; Park, C. H.; Longenecker, K.; Qiu, W.; Torrent, M.; Kovar, P. J.; Bui, M.; et al. (J. Med. Chem., 2020)

(untitled) - Sharp, P. P.; Garnier, J.-M.; Hatfaludi, T.; Xu, Z.; Segal, D.; Jarman, K. E.; Jousset, H.; Garnham, A.; Feutrill, J. T.; Cuzzupe, A.; Hall, P.; Taylor, S.; et al. (ACS Med. Chem. Lett., 2017)

Eur. Pat. Appl. - Cuevas-Cordobés, F.; Pericás-Brondo, M. A. (Tricyclic Triazolic Compounds, 2017)

(untitled) - Armstrong, I.; Aldhumani, A. H.; Schopis, J. L.; Fang, F.; Parsons, E.; Zeng, C.; Hossain, M. I.; Bergmeier, S. C.; Hines, J. V. (Bioorg. Med. Chem., 2020)

PCT Int. Appl. - Ferring, B. V.; Ashworth, D. M.; Pitt, G. R. W.; Hudson, P.; Yea, C. M.; Franklin, R. J.; Semple, G. (Fused Azepine Derivatives And Their Use As Antidiuretic Agents, 2002)

(untitled) - Yan, Z.; Ma, C.; Wang, Y.; Shuai, L.; Guo, Y.; Zhang, L. (Russ. J. Bioorg. Chem., 2022)

Eur. Pat. Appl. - McComas, C. C.; Serrano-Wu, M. H.; Vacca, J. P. (Fused Quadracyclic Compounds, Compositions and Uses Thereof, 2018)

(untitled) - Ma, X. R.; Xu, L.; Xu, S.; Klein, B. J.; Wang, H.; Das, S.; Li, K.; Yang, K. S.; Sohail, S.; Chapman, A.; Kutateladze, T. G.; Shi, X.; et al. (J. Med. Chem., 2021)

(untitled) - Zhong, M.; Peng, E.; Huang, N.; Huang, Q.; Huq, A.; Lau, M.; Colonno, R.; Li, L. (Bioorg. Med. Chem. Lett., 2018)

(untitled) - Shao, C.; Wang, X.; Xu, J.; Zhao, J.; Zhang, Q.; Hu, Y. (J. Org. Chem., 2010)

(untitled) - Özçubukçu, S.; Ozkal, E.; Jimeno, C.; Pericàs, M. A. (Org. Lett., 2009)

(untitled) - Rodionov, V. O.; Presolski, S. I.; Gardinier, S.; Lim, Y.-H.; Finn, M. G. (J. Am. Chem. Soc., 2007)

(untitled) - Lipshutz, B. H.; Taft, B. R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Oliva, A. I.; Christmann, U.; Font, D.; Cuevas, F.; Ballester, P.; Buschmann, H.; Torrens, A.; Yenes, S.; Pericàs, M. A. (Org. Lett., 2008)

(untitled) - Guselnikova, O.; Váňa, J.; Phuong, L. T.; Panov, I.; Rulíšek, L.; Trelin, A.; Postnikov, P.; Švorčík, V.; Andris, E.; Lyutakov, O. (Chem. Sci., 2021)